Analysis and Development of Interface Design on DKI Jakarta & Tangerang‘S Qlue Application based on Don Norman’s 6 Design Principles - Sheila Rizky Novensa; Wira Munggana (Universitas Multimedia Nusantara, 2018)
The Qlue Community App is one of government’s effort to embrace the social media trend. Initial study of user experience showed that there are two things in Qlue App user experience that don’t comply with six design principles from Don Norman’s Design Principles. The two things are constraints and consistency. That was the reason for this research, to analyze and make a better version of user interface for the community service application based on the six design principles from Don Norman. Methodology used in this research is Task-Centered System Design (TCSD). The result of this research is an UI that have a constraint which is a warning page that appeared before user finished writing any report and wanted to go back to previous page. The second result is a consistency of all report writing process and interface including buttons and icons. The conclusion of this research is that the revised proposed user interface has solved the problems that appeared on the UI of Qlue application. Index Terms— Donald Norman, Six Design Principles, Task-Centered System Design, TCSD, User Interface Analysis, Qlue.